2016
DOI: 10.3390/w8060233
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phytodesalination Potential of Vegetated Bioreactors Treating Greenhouse Effluent

Abstract: Abstract:The dissolved salt ions that are not absorbed during irrigation of greenhouse crops are gradually accumulated in the nutrient solution resulting in levels of salinity high enough to damage the crops. This water salinity presents operational and environmental challenges as the nutrient-rich greenhouse effluent should be discharged to the environment when deemed unsuited for irrigation. In this pilot-scale study, the potential of passive salt reduction (phytodesalination) in gravel and wood-chip flow-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…From the point of view of ecosystem services, S. tabernaemontani is important for shoreline protection, erosion control as a stabilizing factor, as a habitat for other species, as well as for providing aeration of sediment and water [235]. In addition, the species has been used in different practical applications of phytoremediation, such as for desalination in bioreactor systems for greenhouse effluent treatment [236].…”
Section: Schoenoplectus Tabarnaemontanimentioning
confidence: 99%
“…From the point of view of ecosystem services, S. tabernaemontani is important for shoreline protection, erosion control as a stabilizing factor, as a habitat for other species, as well as for providing aeration of sediment and water [235]. In addition, the species has been used in different practical applications of phytoremediation, such as for desalination in bioreactor systems for greenhouse effluent treatment [236].…”
Section: Schoenoplectus Tabarnaemontanimentioning
confidence: 99%
“…The study demonstrated that S. portulacastrum showed vigorous growth and high photosynthetic and antioxidant activity in the highly saline condition, which made it a suitable candidate for phytodesalination (Muchate et al 2016). Pouladi et al (2016) performed a pilotscale experiment to assess the phytodesalination potential of seven plant species including Schoenoplectus tabernaemontani, Andropogon gerardii, Typha angustifolia, Elymus canadensis, Panicum virgatum, Spartina pectinata, and Distichlis spicata. The result demonstrated that S. tabernaemontani, and D. spicata, accumulated high concentration of Na + and Cl À compared to T. angustifolia and S. pectinata.…”
Section: 1mentioning
confidence: 99%
“…The synthetic greenhouse effluent was prepared in the laboratory as per the common greenhouse effluent characteristics reported in the literature and by greenhouse operations in Ontario, Canada [4,[16][17][18]. The average influent nitrate concentration was 307 mg N L −1 from day 1 to 387 and 202 mg N L −1 from Day 387 to 936.…”
Section: Bioreactors Set-upmentioning
confidence: 99%